2014
DOI: 10.1002/14651858.cd008998.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests versus clinical diagnosis for managing people with fever in malaria endemic settings

Abstract: Background In 2010, the World Health Organization recommended that all patients with suspected malaria are tested for malaria before treatment. In rural African settings light microscopy is often unavailable. Diagnosis has relied on detecting fever, and most people were given antimalarial drugs presumptively. Rapid diagnostic tests (RDTs) provide a point‐of‐care test that may improve management, particularly of people for whom the RDT excludes the diagnosis of malaria. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 28 publications
3
63
0
Order By: Relevance
“…Of the 13 policy options recommended by the malaria policy brief group, 5 options were eventually accepted after the "evidence synthesis" (ie, synthesising evidence largely from systematic reviews). [40][41][42][43][44][45][46][47] These included the following: (i) Distribution of insecticide treated bednets (ITNs) to be more effective, proper orientation on the usage; (ii) Laboratory diagnosis of malaria to be considered along clinical assessment before treatment of malaria; (iii) artemisinin combination therapies (ACTs) recommended but quality control must be ensured; (iv) More funding for research on indigenous malaria drugs; and (v) Vector control using indoor residual spraying and larval source management. The option on restriction of antimalarial prescription as an over the counter (OTC) drug, was replaced with option that chemists to perform rapid diagnostic test for malaria (RDT) before giving antimalarials (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 13 policy options recommended by the malaria policy brief group, 5 options were eventually accepted after the "evidence synthesis" (ie, synthesising evidence largely from systematic reviews). [40][41][42][43][44][45][46][47] These included the following: (i) Distribution of insecticide treated bednets (ITNs) to be more effective, proper orientation on the usage; (ii) Laboratory diagnosis of malaria to be considered along clinical assessment before treatment of malaria; (iii) artemisinin combination therapies (ACTs) recommended but quality control must be ensured; (iv) More funding for research on indigenous malaria drugs; and (v) Vector control using indoor residual spraying and larval source management. The option on restriction of antimalarial prescription as an over the counter (OTC) drug, was replaced with option that chemists to perform rapid diagnostic test for malaria (RDT) before giving antimalarials (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…4 All the trials were conducted in Africa, indicating that in general, but not in all settings, RDT substantially reduced the over-prescription of antimalarials while not showing a consistent effect on the prescription of antibiotics or the short term outcome for patients.…”
mentioning
confidence: 98%
“…The fact that most people who tested negative on the RDT decided to still take AL also suggests that patients may have lacked confidence in the RDT result. Though our study design is likely to have biased RDT-negative patients toward taking the medicines, several other studies, across different contexts, have also found high prescription and purchase rates of ACTs despite a negative test result, 28,[48][49][50] likely because there is a tendency in malariaendemic areas for both health workers and patients to treat all fever episodes as malaria. [51][52][53] It may be that over time, as patients learn about the accuracy of the test, RDTs will have a greater impact on adherence.…”
Section: Discussionmentioning
confidence: 89%